Pengaruh Kesadaran Halal terhadap Minat Beli Kosmetik Halal - Mella, Sinta Misda (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
Halal cosmetics are products that are increasingly in demand because of consumers' concern about product conformity with religious and health principles. Awareness of halal cosmetic products is an important factor in influencing consumer buying interest. This research aims to identify the influence of halal awareness on interest in purchasing halal cosmetics among consumers. The data collected was analyzed using regression techniques to test the relationship between halal awareness variables and interest in buying halal cosmetics. The research results show that the level of halal awareness significantly influences interest in purchasing halal cosmetics. The implication of this research is the importance of marketing that emphasizes the halal aspects of cosmetic products to attract the interest of consumers who care about the halalness of the products they use.